PENGARUH STATUS KONTAK PASIEN TUBERKULOSIS DENGAN KEJADIAN TUBERKULOSIS PARU: STUDI LITERATUR - Wijayanto, Taufik; Solikhah, Solikhah; Sulistyawati, Sulistyawati (Dian Nuswantoro Semarang, 2023)
Introduction: Tuberculosis remains public health problem worldwide. Pulmonary tuberculosis is an infectious disease that is transmitted from smear-positive pulmonary tuberculoasis patients. Tuberculosis infection has a high risk of being transmitted when there is contact with TB patients. This phenomenon explains that the risk factors for pulmonary tuberculosis transmission are closely related to contact status with tuberculosis patients. Methods: Literature review was carried out by searching articles through electronic databases (Google Scholar, PubMed, ScienceDirect, and SpringerLink) using the keywords tuberculosis contact status, risk factors for tuberculosis events, and contact status AND incident of pulmonary tuberculosis. The inclusion criteria for the articles used were articles published in accredited national and international publication articles, the year of publication of the article in the 2017-2023 range, full text, open access, and no restrictions related to research design in the article. Nine articles were selected for analysis. Articles are analyzed using matrix tables and Prism schemes. Results: Based on a literature review, it was found that there was an effect of contact status on the incidence of pulmonary tuberculosis. Contact status with tuberculosis -infected patients affects the incidence of pulmonary tuberculosis transmission. Contact with tuberculosis patients can occur in the household, hospital environment, and school. Conclusion: Based on the literature study, it is explained that the status of contact with tuberculosis patients significantly affects and has a high risk of developing pulmonary tuberculosis.Keywords: Contact status, Literature review, Pulmonary tuberculosis